Neuroplasticity in addiction: cellular and transcriptional perspectives - Madsen, Heather; Brown, Robyn; Lawrence, Andrew (Frontiers in Molecular Neuroscience, 2012)
Drug addiction is a chronic, relapsing brain disorder which consists of compulsive patterns of drug-seeking and taking that occurs at the expense of other activities. The transition from casual to compulsive drug use and the enduring propensity to relapse is thought to be underpinned by long lasting neuroadaptations in specific brain circuitry, analogous to those that underlie long-term memory formation. Research spanning the last two decades has made great progress in identifying cellular and molecular mechanisms that contribute to drug-induced changes in plasticity and behaviour. Alterations in synaptic transmission within the mesocorticolimbic and corticostriatal pathways, and changes in the transcriptional potential of cells by epigenetic mechanisms are two important means by which drugs of abuse can induce lasting changes in behaviour. In this review we provide a summary of more recent research that has furthered our understanding of drug-induced neuroplastic changes both at the level of the synapse, and on a transcriptional level, and how these changes may relate to the human disease of addiction.